Distinct Campylobacter fetus lineages adapted as livestock pathogens and human pathobionts in the intestinal microbiota. Issue 1 (December 2017) - Iraola, Gregorio; Forster, Samuel; Kumar, Nitin; Lehours, Philippe; Bekal, Sadjia; García-Peña, Francisco; Paolicchi, Fernando; Morsella, Claudia; Hotzel, Helmut; Hsueh, Po-Ren; Vidal, Ana; Lévesque, Simon; et al.
Abstract Campylobacter fetus is a venereal pathogen of cattle and sheep, and an opportunistic human pathogen. It is often assumed thatC. fetus infection occurs in humans as a zoonosis through food chain transmission. Here we show that mammalianC. fetus consists of distinct evolutionary lineages, primarily associated with either human or bovine hosts. We use whole-genome phylogenetics on 182 strains from 17 countries to provide evidence thatC. fetus may have originated in humans around 10, 500 years ago and may have "jumped" into cattle during the livestock domestication period. We detectC. fetus genomes in 8% of healthy human fecal metagenomes, where the human-associated lineages are the dominant type (78%). Thus, our work suggests thatC. fetus is an unappreciated human intestinal pathobiont likely spread by human to human transmission. This genome-based evolutionary framework will facilitateC. fetus epidemiology research and the development of improved molecular diagnostics and prevention schemes for this neglected pathogen. Human infections withCampylobacter fetus are often assumed to be derived from livestock. Here, Iraola et al. provide evidence that healthy humans may act as carriers and dispersers, andC. fetus may have originated in humans as an intestinal pathobiont and then adapted as a livestock pathogen.